TINJAUAN DUE PROCES OF LAW ATAS TINDAKAN PENEGAK HUKUM TERHADAP DISKRIMINASI MASYARAKAT PAPUA PERSPEKTIF SIYASAH SYAR’IYYAH - Reynaldi, Muh; Larissa, Dea (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2024)
Law enforcement in Papua is not running in accordance with the values of legal philosophy, and the struggle of the Papuan people for justice is still not over. The many cases of law enforcement officers using violence and cruelty against the Papuan people show a tendency towards prejudice in the field of law enforcement. This study seeks to determine the actions of law enforcement officials against the Papuan people in accordance with the principle of due process of law and the perspective of siyasah syar'iyyah towards law enforcement officials for discrimination against the Papuan people through the use of library research, with a normative syar'i and normative juridical approach. The results of this study indicate that the actions of law enforcement against the Papuan people often spark controversy because they are considered to violate the principles of due process of law in several cases handled without following established protocols. The importance of upholding the ideals of justice and equality and the protection of human rights is emphasized in siyasah shar'iyyah. To uphold the dignity of the rule of law, the government and law enforcement agencies must take a firm stance against prejudice against Papuans and must also improve the standard of legal education provided to law enforcement officials.